Thermal adaptation and clinal mitochondrial DNA variation of European anchovy - Silva, Goncalo (2018)
Natural populations of widely distributed organisms often exhibit genetic clinal variation over their geographical ranges. The European anchovy, Engraulis encrasicolus, illustrates this by displaying a two-clade mitochondrial structure clinally arranged along the eastern Atlantic. One clade has low frequencies at higher latitudes, whereas the other has an anti-tropical distribution, with frequencies decreasing towards the tropics. The distribution pattern of these clades has been explained as a consequence of secondary contact after an ancient geographical isolation. However, it is not unlikely that selection acts on mitochondria whose genes are involved in relevant oxidative phosphorylation processes. In this study, we performed selection tests on a fragment of 1044 bp of the mitochondrial cytochrome b gene using 455 individuals from 18 locations. We also tested correlations of six environmental features: temperature, salinity, apparent oxygen utilization and nutrient concentrations of phosphate, nitrate and silicate, on a compilation of mitochondrial clade frequencies from 66 sampling sites comprising 2776 specimens from previously published studies. Positive selection in a single codon was detected predominantly (99%) in the anti-tropical clade and temperature was the most relevant environmental predictor, contributing with 59% of the variance in the geographical distribution of clade frequencies. These findings strongly suggest that temperature is shaping the contemporary distribution of mitochondrial DNA clade frequencies in the European anchovy.